1997
DOI: 10.1155/s1023621x98000013
|View full text |Cite
|
Sign up to set email alerts
|

Heat (Mass) Transfer in a Rotating Two‐Pass Square Channel — Part II:Local Transfer Coefficient, Smooth Channel

Abstract: Naphthalene sublimation technique and the heat/mass transfer analogy are used to determine the detailed local heat/mass transfer distributions on the leading and trailing walls of a twopass square channel with smooth walls that rotates about a perpendicular axis. Since the variation of density is small in the flow through the channel, buoyancy effect is negligible. Results show that, in both the stationary and rotating channel cases, very large spanwise variations of the mass transfer exist in he turn and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…More detailed information on the local heat transfer distribution is provided by the studies of Kukreja et al (Kukreja et al, 1998) and . In the former study the authors, by using the naphthalene sublimation technique, obtained detailed local heat/mass transfer distributions on the smooth walls of two pass square channel with 180° sharp turn while, in the latter one, by using water as working fluid, they analyzed both the convective heat transfer distribution by means of the transient liquid crystal technique and the flow field by Quantitative InfraRed Thermography Journal 2007.4:41-62.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed information on the local heat transfer distribution is provided by the studies of Kukreja et al (Kukreja et al, 1998) and . In the former study the authors, by using the naphthalene sublimation technique, obtained detailed local heat/mass transfer distributions on the smooth walls of two pass square channel with 180° sharp turn while, in the latter one, by using water as working fluid, they analyzed both the convective heat transfer distribution by means of the transient liquid crystal technique and the flow field by Quantitative InfraRed Thermography Journal 2007.4:41-62.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, axial velocity and heat transfer near the leading surface is higher than that around trailing surface in the radial inward flow passage. Kukreja et al (1998) adopted Naphthalene sublimation technique to analyse the mass transfer distribution on the leading and trailing walls of a U-shaped square smooth passage. The results showed that Coriolis forces improved mass transfer near the trailing side of the radial outward channel, but declined the mass transfer near the leading wall of radial inward pass.…”
Section: Effect Of Coriolis Forcementioning
confidence: 99%
“…Then, many researchers started to investigate the heat transfer in a rotating channel. Kukreja et al 5 used the Naphthalene sublimation technology to investigate a rotating two-pass square channel. They also found that the rotation-induced Coriolis increases the mass transfer on the trailing wall and reduces the mass transfer on the leading wall.…”
Section: Introductionmentioning
confidence: 99%